2016
DOI: 10.7717/peerj.2656
|View full text |Cite
|
Sign up to set email alerts
|

Foliar fungal communities strongly differ between habitat patches in a landscape mosaic

Abstract: BackgroundDispersal events between habitat patches in a landscape mosaic can structure ecological communities and influence the functioning of agrosystems. Here we investigated whether short-distance dispersal events between vineyard and forest patches shape foliar fungal communities. We hypothesized that these communities homogenize between habitats over the course of the growing season, particularly along habitat edges, because of aerial dispersal of spores.MethodsWe monitored the richness and composition of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 72 publications
0
25
2
Order By: Relevance
“…The relative abundance of the pathogen was much higher in our study (between 15 to 70% depending on the tissue type) than in other studies of grapevine foliar fungal communities, where it represented less than 5% Gobbi et al 2020). Several factors, including leaf age and sampling date, might account for this difference as there is marked turnover in the grapevine foliar fungal community along the vegetative season (Pinto & Gomes 2016;Fort et al 2016;Gobbi et al 2020). The artificial inoculation of the pathogen on some vines at the beginning of the vegetative season is also probably responsible for the higher relative abundance of the pathogen in our study.…”
Section: Discussioncontrasting
confidence: 67%
“…The relative abundance of the pathogen was much higher in our study (between 15 to 70% depending on the tissue type) than in other studies of grapevine foliar fungal communities, where it represented less than 5% Gobbi et al 2020). Several factors, including leaf age and sampling date, might account for this difference as there is marked turnover in the grapevine foliar fungal community along the vegetative season (Pinto & Gomes 2016;Fort et al 2016;Gobbi et al 2020). The artificial inoculation of the pathogen on some vines at the beginning of the vegetative season is also probably responsible for the higher relative abundance of the pathogen in our study.…”
Section: Discussioncontrasting
confidence: 67%
“…For example, Jumpponen and Jones (2010) have also shown that fungal communities in the phyllosphere of Quercus macrocarpa are greatly influenced by site conditions. Fort et al (2016) have shown that the microclimate is among the major factors that might account for differences in foliar fungal communities between sites. Although the number of fungal taxa detected in our study was high (1017 fungal taxa) and comparable to similar phyllosphere fungi studies in different tree species Figure 3.…”
Section: Discussionmentioning
confidence: 99%
“…The spatial variations and temporal dynamics of endophytic fungal communities have been studied frequently in the past few years (Martins et al, 2016;Mishra et al, 2012;Scholtysik, Unterseher, Otto, & Wirth, 2013). Earlier studies have also indicated that the differences between endophytic communities of different habitats are mainly resulted from environmental characteristics such as microclimate and host plant (Fort, Robin, Capdevielle, Delière, & Vacher, 2016;Loro, Valero-Jiménez, Nozawa, & Márquez, 2012;Mulder & de Zwart, 2003). Earlier studies have also indicated that the differences between endophytic communities of different habitats are mainly resulted from environmental characteristics such as microclimate and host plant (Fort, Robin, Capdevielle, Delière, & Vacher, 2016;Loro, Valero-Jiménez, Nozawa, & Márquez, 2012;Mulder & de Zwart, 2003).…”
Section: Fungal Endophytes Organ Preference and Ecological Patternsmentioning
confidence: 99%
“…In this case, studied sites had similar forest structure, elevation range and climate which possibly led to relatively similar fungal communities in Q. brantii organs with similar diversity (Figure 3b). Earlier studies have also indicated that the differences between endophytic communities of different habitats are mainly resulted from environmental characteristics such as microclimate and host plant (Fort, Robin, Capdevielle, Delière, & Vacher, 2016;Loro, Valero-Jiménez, Nozawa, & Márquez, 2012;Mulder & de Zwart, 2003). (Robinson, 2001).…”
Section: Fungal Endophytes Organ Preference and Ecological Patternsmentioning
confidence: 99%